Liturgy in Postcolonial Perspectives
XI, 319 p.
Keywords: This book brings Christian, Jewish and Muslim scholars from different fields of knowledge and many places across the globe to introduce/expand the dialogue between the field of liturgy and postcolonial/decolonial thinking. Connecting main themes in both fields, this book shows what is at stake in this dialectical scholarship.